2003
DOI: 10.1029/2002ja009511
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the magnetic cloud boundary layers

Abstract: [1] Based on a statistical analysis of the boundary physical states of 80 magnetic clouds reported in the literature from the years 1969 to 2001, we suggest a new identification of the magnetic cloud boundary by describing it as front and tail boundary layers (BLs) formed through the interaction between the magnetic cloud and the ambient medium. In our identification the outer boundary of the layer often displays the properties of magnetic reconnection, which could be characterized by a ''three-high state'' (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 56 publications
3
88
0
Order By: Relevance
“…In most cases the boundary is far from that clear. A statistical study of 80 MCs by Wei et al (2003a) showed that the majority of them were bounded by boundary layers with average passage durations of 1.7 and 3.1 h at the front and rear edges, respectively. The right-hand side of Fig.…”
Section: Identifying Icme Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases the boundary is far from that clear. A statistical study of 80 MCs by Wei et al (2003a) showed that the majority of them were bounded by boundary layers with average passage durations of 1.7 and 3.1 h at the front and rear edges, respectively. The right-hand side of Fig.…”
Section: Identifying Icme Boundariesmentioning
confidence: 99%
“…In the left-hand panels the dashed vertical line indicates the sharp boundary and in the right-hand panels the pair of dashed lines marks a wider boundary layer. Both cases are discussed in Wei et al (2003a) magnetic field direction. As noted by Wei et al (2003a) these are common features of boundary layers and can be interpreted as signatures of magnetic reconnection.…”
Section: Identifying Icme Boundariesmentioning
confidence: 99%
“…Regions of depressed magnetic fields are also occasionally observed at the leading edges of magnetic clouds (Wei et al, 2003). These depressions are localized regions where the IMF magnitude is depressed well below average accompanied by a simultaneous increase in plasma pressure.…”
Section: Discussionmentioning
confidence: 91%
“…As a significant fraction of MCs occur close to the interplanetary magnetic field (IMF) sector boundaries and are followed by high-speed streams (Crooker et al, 1998;Fenrich and Luhmann, 1998), the distortion of the MC structure by the following high-speed stream is a common scenario. Substructures have also been used to define MC front boundaries (Wei et al, 2003) and to separate MCs from ICME-related plasma ahead (Farrugia et al, 2001;Kilpua et al, 2013a). According to above-described studies the analysis of MC substructures may yield important information on the history of the interaction between the MC and the ambient solar wind as well as on the CME release process.…”
Section: Introductionmentioning
confidence: 99%
“…However, a boundary layer of a MC is an extended region (see Wei et al, 2003) and the actual MC boundary is usually rather abrupt as the spacecraft flies through it, so an identification of a boundary layer should have limited usefulness for our method. It is mainly for this reason that we did not add the possible existence of a boundary layer to our scheme.…”
Section: Summary and Discussionmentioning
confidence: 99%